Managing Engineering and Technology (International Edition) : International Edition - Morse, Lucy C.; Babcock, Daniel L. (Pearson International Content, 2014)
For courses in Technology Management, Engineering Management, or Introduction to Engineering Technology. Managing Engineering and Technology is designed to teach engineers, scientists, and other technologists the basic management skills they will need to be effective throughout their careers. The full text downloaded to your computer With eBooks you can: search for key concepts, words and phrases make highlights and notes as you study share your notes with friends eBooks are downloaded to your computer and accessible either offline through the Bookshelf (available as a free download), available online and also via the iPad and Android apps. Upon purchase, you'll gain instant access to this eBook. Time limit The eBooks products do not have an expiry date. You will continue to access your digital ebook products whilst you have your Bookshelf installed.